2019
DOI: 10.1098/rsos.190003
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent development of the blow fly Chrysomya pinguis and its significance in estimating postmortem interval

Abstract: Chrysomya pinguis (Walker) (Diptera: Calliphoridae) is an endemic Asiatic blow fly species of forensic importance. Chrysomya pinguis is one of the first species to colonize a corpse, especially in high altitude areas during spring and autumn when the ambient temperature is lower. Despite its potential for forensic investigations to estimate the minimum postmortem interval (PMI min ), little is known about the development of C. pinguis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
1
11
0
1
Order By: Relevance
“…In other dipteran larvae such as Lucilia sericata, it has been shown that aggregation leads to a shorter development time due to heat production [24]. This aspect of larval growth was intensively investigated in forensic entomology, where the relationship between development time and temperature is used to calculate the age of sampled insects and, thus, estimate the minimum post mortem interval (PMImin) [54]. In BSF production processes, understanding this relationship which was shown to differ among scales and densities, could help optimize the larval growth condition making the larvae production and/or waste processing more time and energy-efficient.…”
Section: Discussionmentioning
confidence: 99%
“…In other dipteran larvae such as Lucilia sericata, it has been shown that aggregation leads to a shorter development time due to heat production [24]. This aspect of larval growth was intensively investigated in forensic entomology, where the relationship between development time and temperature is used to calculate the age of sampled insects and, thus, estimate the minimum post mortem interval (PMImin) [54]. In BSF production processes, understanding this relationship which was shown to differ among scales and densities, could help optimize the larval growth condition making the larvae production and/or waste processing more time and energy-efficient.…”
Section: Discussionmentioning
confidence: 99%
“…This was based upon the estimation that at an average temperature in Darwin of ~25°, the most numerous genera of blow fly in northern Australia (Chrysomya spp.) would complete their lifecycle in around 12 days (Byrd & Butler 1997;Zhang et al 2019) and begin egg laying after another 5-7 days (Gabre et al 2005;Hadura et al 2018).…”
Section: Stink Stations and Flower Visitationmentioning
confidence: 99%
“…The differentiation between different larval stages of blowflies was not done here, so we gave the general time range (23-72 hours) for development from the first instar to the third instar larvae. If we compare the blowfly's larval development between the average temperature range 16°-22°C, then the time taken for the appearance of the first instar to the third instar comes in the range of 52-96 hours (Zhang et al 2019). Therefore, the larvae found on the body of the red fox might be 2-4 days old.…”
Section: Discussionmentioning
confidence: 99%